Implementasi Keamanan Citra Menggunakan Algoritma AES-128 Dengan Aplikasi Client-Server - Azanuddin, A; Yakub, Suardi; Prayudha, Jaka (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2022)
Digital images that are private and confidential are very vulnerable to eavesdropping by irresponsible parties. Especially when distributed over the internet, such as chat-based applications such as Facebook, WhatsApp and e-mail media. Image sent via the internet. Because digital images are still recognizable images and can be used by eavesdroppers for personal gain, to the detriment of those who have access to image data. The act of tapping the image data can be minimized by the application of cryptographic encryption techniques. This research will secure digital images with 128 bit AES method for encryption and decryption of digital images in client-server based applications. The results of the AES algorithm encryption produce a cipherimage with pixel values that are much different from the plainimage pixel values.